The effect of preseason sport camp on strength and speed abilities in youth swimmers - Bielec, Grzegorz (2025)
Introduction. Regular assessment of anthropometric variables and motor fitness of young athletes is an integral part of the training process. However, the physiological effects of seasonal sport camps on youth athletes have not been investigated thoroughly. Objective. The aim of the current study is to assess the changes in strength and speed performance in youth swimmers resulting from a short-term preseason camp. Methods. Eleven swimmers aged 13-14 years participated in an 8-day camp. The camp programme included nine training sessions in the swimming pool, five general fitness training sessions in the athletics stadium, and two strength circuit training sessions. Participants were interviewed to determine the amount of physical activity undertaken in summer vacation. Fitness tests were conducted on the 1st day and were repeated on the 8th day of camp. Participants performed the following motor tests: a 50-m dash, bent-arm hang, a hand grip test, and a 100-m front crawl trial. Results. Participants improved their swimming speed (p<0.001) but worsened their grip strength (p=0.04). No significant changes were noted in the results of the 50-m dash test (p=0.90) and the bent-arm hang test (p=0.30). Anthropometric variables were not correlated substantially with any result of motor performance. Participation in physical activity during summer break was negatively correlated with swimming performance (r=-0.66; p<0.05) and positively correlated with grip strength (r=0.70; p<0.05). Conclusions. Improvement in swimming speed was the most important outcome of the preseason camp for youth athletes. Endurance-oriented training loads may have caused the lack in improvement of muscular strength. The amount of physical activity undertaken during summer vacation had an impact on motor performance in youth swimmers.